2021
DOI: 10.1097/acm.0000000000004357
|View full text |Cite
|
Sign up to set email alerts
|

Defining Successful Practice Within Health Systems Science Among Entering Residents: A Single-Institution Qualitative Study of Graduate Medical Education Faculty Observations

Abstract: PurposeThe American Medical Association's Accelerating Change in Medical Education consortium defined health systems science (HSS) as the study of how health care is delivered, how health care professionals work together to deliver that care, and how the health system can improve patient care and health care delivery. This framework is increasingly being incorporated into medical school curricula. Graduate medical education (GME) had previously elevated systems-based practice (SBP) as a core competency, but ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…This multi-institutional study supports the previously described Logic model framework for HSS 4,5 and reinforces that precurricular background including medical school exposures to HSS are preparatory for residency. This study suggests that GME learning environments, rather than specialties, are the determining factor in whether faculty observe specific HSS skills in the workplace.…”
Section: Discussionsupporting
confidence: 87%
“…This multi-institutional study supports the previously described Logic model framework for HSS 4,5 and reinforces that precurricular background including medical school exposures to HSS are preparatory for residency. This study suggests that GME learning environments, rather than specialties, are the determining factor in whether faculty observe specific HSS skills in the workplace.…”
Section: Discussionsupporting
confidence: 87%
“…[19][20][21][22][23] Existing research suggests medical students prefer patient care activities over systems improvement activities, 24,25 and residents struggle to understand the vision and purpose of quality improvement within health systems. 26 While some residents excel within particular HSS domains, 27 milestone-based ratings of performance during internship do not differ between graduates of medical schools with and without HSS curricula. 28 This could in part reflect a limited sensitivity of milestone-based assessments 28 and also suggests that factors outside the HSS curriculum may contribute to identification with systems-related roles.…”
Section: Discussionmentioning
confidence: 97%
“…[61][62][63][64] and variable uptake and understanding of systems-related activities among residents and practicing physicians. 26,27,[65][66][67][68] Professional identity formation transforms learners from members of the lay public into professionals who "think, act, and feel" like a physician. 29,30 Prior studies have identified formative experiences contributing to this process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Ridinger and colleagues demonstrated, we have much to learn on how to teach and prepare trainees for long-valued but seldom well-taught foundational disciplines like health systems science. 18 Their realist-inspired study of faculty members' experiences in training residents in health systems sciences provides a conceptual road map for the design of future curricula in health systems science.…”
Section: Innovation As a Solution … And A Problemmentioning
confidence: 99%